Emergence of Colistin Resistance in Extended-Spectrum Beta-Lactamase-Producing Escherichia coli Isolates from Dairy Cows in Türkiye - Günaydin, Elçin; Önat, Kaan; Kaynar, Pınar Mursaloğlu; Goncagül, Gülşen (Sciencedomain International, 2024)
Background: In recent years, the reporting of extended-spectrum beta-lactamase producing and colistin-resistant Escherichia coli (E. coli)  in food-producing livestock animals is of great importance as a potential vector of multi-drug resistant (MDR) E. coli for the farm environment, farm workers, and veterinarians who are in close contact with these animals. In this study, it was aimed to determine antibiotic resistance profiles of E. coli from diarrhoeic dairy cows,  and observe the resistance against beta-lactam group antibiotics and colistin in 3 years’ time. Materials and Methods: For the isolation, 1g of sample was suspended into 9 mL of modified Tryptone Soya Broth and incubated overnight at 37 °C. After the incubation, the broth was inoculated on MacConkey Agar and EMB Agar and incubated aerobically at 37 °C for 24h. Identification was done according to biochemical tests. E. coli isolated from the fecal samples of diarrhoeic dairy cows were investigated for the antibiotic resistance with the six different antibiotic classes by Kirby Bauer Disc Diffusion Test. Results: Fifty-four E. coli isolated from the fecal samples of diarrhoeic dairy cows were investigated for the multi-drug resistance. Fourty-four E. coli showed MDR resistance, including colistin; nine E. coli isolates showed MDR resistance profiles involving at least six to ten antibiotics , but not for colistin. It was discovered that MDR E. coli isolates were also resistant to colistin. Resistance to beta-lactams were observed 100% in 2021 and 2022, but not for 2020. Colistin resistance was found to have increased progressively year over year, reaching 0% in 2000 and 37.03% and 46.29% in the next two years, respectively. Conclusion: As a conclusion, circulation of beta-lactamase producing E. coli accompanied with colistin resistant E. coli in live-stock animals reared for the purpose of milk production should be concerned as a potential public health problem in terms of one health concept and more detailed investigations should be planned to question the ground origins of gradual increase.
Keywords: [SHS.ANTHRO-BIO] Humanities and Social Sciences/Biological anthropology